A review of the distribution of the crested eagle, Morphnus guianensis (Daudin, 1800) (Accipitridae: Harpiinae), including range extensions - Gomes, Felipe Bittioli Rodrigues; Sanaiotti, Tânia Margarete (Revista Brasileira de Ornitologia, 2015)
Here we review the distribution of the Crested Eagle (Morphnus guianensis) in the Americas, and based on the Brazilian Harpy Eagle Conservation Program (PCGR) database, literature, online databases, zoos, wild and museum records, we provide an updated distribution map with 37 points outside the IUCN map; 16 were recorded close to the border of the map (up to 40 km), and do not expand or contribute to the distribution map. Far from the border (>40 km) we found 21 records, contributing to an expansion of the known range and habitat. At the northernmost extreme of distribution, the range was extended to southern Mexico; in Nicaragua, the range extension was farther south in the north, and two records extend the range to the southern border with Costa Rica. In Colombia, an old specimen is located between Darien Peninsula and the Perija Mountains. In Brazil a record from the ecotone between Cerrado and Gallery Forest, and another in an upland remnant of Atlantic Rainforest, expands the range towards central and southeastern Brazil, and to the Northeast, old records could expand the Atlantic Rainforest distribution towards the interior. © 2015, Sociedade Brasileira de Ornitologia. All rights reserved.
Keywords: Conservation Management; Ecotone; Geographical Distribution; Habitat Type; International Organization; Literature Review; Mapping Method; Range Expansion; Raptor; Record; Central America; Mexico [north America]; South America; Accipitridae; Falconiformes; Harpia Harpyja; Morphnus Guianensis; Raptores